FORMULATION AND PHYSICAL EVALUATION OF BALSAM PREPARATIONS FROM ROSEMARY ESSENTIAL OIL (ROSMARINUS OFFICINALIS L.) - Huzima, Winda; Rini, Tri Diana Puspita (Gamma Publishing, 2025)
Rosemary essential oil (Rosmarinus officinalis L.) has the potential as a medicine because it contains chemical compounds 1,8-cineol, camphor, α-pinene limonene, camphene and linalool which work as analgesics and aromatherapy. One of the pharmaceutical preparations that can be used as an analgesic and aromatherapy is a balm preparation because the balm preparation can overcome mild pain and stress. This study aims to determine the effect of cera alba and menthol concentrations on the physical properties of the balm, and to determine the most optimum concentration of cera alba and menthol. The sample used was ylang-ylang essential oil. Rosemary essential oil was made into a balm preparation in 5 formulations with variations of cera alba 5% -11% and menthol 1% -7%. The five formulations were tested for their physical properties including organoleptic, homogeneity, pH, adhesion and spreadability. The test results were used to find the optimum formula using the simplex lattice design (SLD) method and the five formulations obtained one best formula, namely formulation 5 with a concentration of cera alba 5% and Menthol 6%.